ANALISIS HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS KARYAWAN - Fauzia Tutupoho (P3M Politeknik Negeri Ambon, 2025)
The era of globalization and increasingly fierce business competition requires organizations to optimize employee productivity as a strategic asset in achieving competitive advantage. Previous research shows gaps in the literature regarding the simultaneous relationship mechanisms between transformational leadership, job satisfaction, and organizational commitment to employee productivity in the context of Indonesian organizational culture. This study aims to analyze the influence of transformational leadership, job satisfaction, and organizational commitment on employee productivity, as well as examine the mediating role of job satisfaction and organizational commitment in the relationship between transformational leadership and employee productivity. The study uses a quantitative approach with explanatory research type, involving 35 employee respondents selected through purposive sampling. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using Structural Equation Modeling with Partial Least Square (PLS-SEM) approach through SmartPLS 4.0 software. The structural model explains 63.7% of employee productivity variance. Job satisfaction has the most dominant influence on productivity (β = 0.367, p = 0.004), followed by organizational commitment (β = 0.312, p = 0.015) and transformational leadership (β = 0.284, p = 0.031). Transformational leadership strongly influences job satisfaction (β = 0.621, p < 0.001) and organizational commitment (β = 0.354, p = 0.026). Job satisfaction proves to be a partial mediator with VAF 44.5% in the relationship between transformational leadership and employee productivity. Transformational leadership, job satisfaction, and organizational commitment significantly influence employee productivity. Organizations are recommended to implement comprehensive transformational leadership development programs and focus on improving job satisfaction as the main strategy to enhance sustainable productivity.Keywords: Employee Productivity; Job Satisfaction; Organizational Commitment; Structural Equation Modeling; Transformational Leadership